ESTUDIOS DE TAXONOMIA MOLECULAR EN POBLACIONES DE TRIATOMA INFESTANS (KLUG, 1934) Y TRIATOMA SPINOLAI PORTER, 1933 (HEMIPTERA: TRIATOMINAE) (Acta Entomológica Chilena, 2022)
The enzymalic movililv differences belween Trialuma infestan* and T. spmnlat are described in ihis paper.Funhermore, the differences in genetic frequencies in bolh species are also discussed. For each speciesihe idenlity and genelic distance coefficient is calculated. T he taxonomic status of these populations istoo discussed.